Profitability Analysis of Non-Timber Forest Products Marketing in Eastern Hills of Nepal: Looking for an Alternative Marketing Approach to Benefit the Poor - Pandit, BH; Subedi, R; Kumar, C (The Initiation, 2010)
Key words: Nepal; NTFP trading; profitability; poor people; collectors; traders DOI: 10.3126/init.v1i0.2675 The Initiation Vol.1 2007 p.16-28